Pressure Sensor Stability Analysis of Positive End Expiratory Pressure Parameters in Flow Analyzer Design - Levana Forra Wakidi; Abd Kholiq; Eko Dedi Prasetyo; Chandrasekaran P (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2023)
The Positive End Expiratory Pressure (PEEP) parameter is a parameter that must be considered in the process of determining the patient's condition, a safe threshold, and must be in accordance with the settings. However, often the PEEP value on the ventilator does not match the settings so that the measuring instrument capable of detecting PEEP on the ventilator is the Flow Analyzer. The purpose of this study was to design a Flow Analyzer using the MPX2010 sensor to analyze the stability of the PEEP parameters on the ventilator. This study used PEEP settings of 0, 5, 8, 11, 14, 17, 20, 23, 26, and 29 cmH2O. Data were collected using a ventilator with VCV (Volume Control Ventilation) and PCV (Pressure Control Ventilation) modes. The tool used for reference from standard measurements uses the Standard Flow Analyzer tool. The results of this study indicate that the measurement accuracy of PEEP parameters with the Flow Analyzer module at each PEEP setting has the smallest error of ±0% at 0 cmH2O setting so that it also has the smallest value of 0 by standard. deviation and uncertainty (UA) value 0 at each setting. The Flow Analyzer measurement module has the largest error in the 5 cmH2O setting, which is ±13.2% with the largest correction value of 0.77. From the data obtained, it can be said that the monitoring of the PEEP parameter is quite stable even though the value is still out of tolerance. Monitoring of PEEP stability parameters can be implemented during the ventilator calibration process which needs to be carried out to analyze damage and reduce the time of damage to the ventilator.